Customer tolerance in homestays: The influence of interpersonal interaction and motivation Attribution - Huiling Zhou; Longfang Huang; Yu Guo; Yajun Jiang; Ke Wu (PLoS ONE, 2025)
Customer tolerance behavior actively sustains harmonious host–guest relationships and strengthens homestay reputations. Drawing on social cognition theory and attribution theory, this study investigates how interpersonal interaction shapes customer tolerance behavior in homestay services and examines whether stay duration moderates these effects. Using survey data from 322 homestay customers collected via the Credamo platform, we test the mechanisms linking interaction quality, motivational attribution, and tolerance. Our findings reveal that interpersonal interaction significantly enhances customer tolerance behavior. Specifically, interaction encourages customers to attribute altruistic rather than self-interested motives to hosts, and these attributions mediate the effect of interaction on tolerance. Although stay duration amplifies the direct effect of interaction on tolerance, it does not significantly moderate the link between interaction and motivational attribution. These findings clarify the psychological processes driving tolerance in homestay contexts and highlight the importance of cultivating positive host–guest interactions to build service resilience.